4-H School Enrichment: A Guide for 4-H Faculty and Staff - Tracy A. Tesdall (EDIS, 2012)
A partnership with the schools extends the 4‑H program to more youth through a unique delivery mode. Since School Enrichment may be a new experience for some Extension agents, this 8-page guide presents some strategies for developing a partnership with the schools and for programming. Written by Tracy A. Tesdall and published by the 4-H Youth Development Program, September 2012.